Investigation of wireless magnetometer in sensing magnetic field changes at different car direction and speed - Chin Fhong Soon; Siti Hajar Aminah Ali; See Khee Ye; Munzilah Md Rohani; Kian Sek Tee; Marlia Morsin; Nafarizal Nayan; Chiok Chuan Lim (Bulletin of Electrical Engineering and Informatics, 2021)
The embedment of induction loop underground for traffic volume monitoring caused damaging effects to the road and reduced road surface aesthetics. A wireless magnetometer implanted underground in a small uniform area was developed to detect three-axis magnetic flux changes due to the perturbation of vehicle passing over the sensor. In this project, a wireless magnetometer sensor system operating at a radio frequency of 2.4 GHz for detecting and transmitting Z-field data has been developed to investigate the patterns of magnetic field associated with the car directions and speed. This is the first report in revealing the responses of the sensor to different car speed and sensing directions. Field tests were conducted by car passes over in a direction in-line or countering the X and Y axes of the magnetometer. The results showed that the strong magnetic field density as low as -100 to -230 μT could be generated when a car passed over the sensor in a direction countering X and Y axes. The speed detection limit of the sensor is less than 60 kmph. The X, Y and Z flux patterns obtained is import in designing an algorithm for accurate detection and counting of vehicles.